Method for measuring contents of nylon fibers and mucilage in nylon cotton

By dissolving nylon cotton fragments in formic acid and separating fibers and glue, and measuring their fiber-powder ratio, the problem of inaccurate measurement of nylon fibers and glue content in nylon cotton in the prior art is solved, and the quality of nylon wheels is achieved Uniformity and convenience of quality control of manufacturers.

CN119437988APending Publication Date: 2025-02-14YANGJIANG WEIYI POLISHING MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411798884.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to accurately measure the content of nylon fiber and glue in nylon cotton, resulting in uneven quality of nylon wheels, making it difficult for manufacturers to control the quality and unable to stably output high-quality nylon wheels.

Method used

The solid-liquid fragments of nylon cotton after the glue were added to formic acid and dissolved, and then the solid-liquid phases were separated by vacuum filtration and drying steps to obtain the glue powder, and the fibers of nylon fiber and glue powder were calculated by weighing. Pink comparison.

Benefits of technology

The accurate measurement of the content of nylon fiber and glue powder in various nylon cotton is achieved, ensuring the consistency of quality of nylon wheels, bringing convenience of quality control to the manufacturer, and being able to stably output high-quality nylon wheels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119437988A_ABST
    Figure CN119437988A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nylon cotton detection, in particular to a method for measuring the content of nylon fibers and mucilage in nylon cotton, which comprises the following steps: material preparation: weighing nylon cotton fragments; dissolving: adding the nylon cotton fragments into formic acid; solid-liquid separation: carrying out suction filtration on the soaked mixed solution by using a vacuum suction filtration method, and drying the filtered solid to obtain mucilage powder; weighing: weighing the dried mucilage powder; and calculating the fiber powder ratio: calculating the fiber powder ratio according to the corresponding data. According to the invention, the contents of nylon fibers and mucilage powder at each part of nylon cotton can be conveniently and accurately mastered, so that the quality of each part of the nylon cotton can be conveniently and accurately mastered, the nylon wheels with required quality can be correspondingly produced according to the quality of each part of the nylon cotton, and the nylon wheels with different qualities can be conveniently classified and managed; according to the device, great convenience can be brought to control over the quality of the nylon wheel by a production enterprise, and the production enterprise can conveniently and stably output the high-quality nylon wheel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nylon cotton detection, in particular to a method for measuring the content of nylon fiber and glue in nylon cotton. Background Art

[0002] At present, nylon cotton that has been sprayed with glue and cured is used in the production of nylon wheels for grinding and polishing. Among them, the mass ratio of nylon fiber to glue in nylon cotton is directly related to the quality of nylon wheels. For this reason, in the production process of nylon wheels, it is necessary to accurately grasp the content of nylon fiber and glue. However, now the approximate mass ratio of nylon fiber and glue powder in nylon cotton is calculated by calculating the mass of sprayed glue and the amount of fiber used by feeding the carding machine. This method of grasping the content of nylon fiber and glue cannot accurately reflect the mass ratio of glue and fiber in each part of nylon cotton, but can only calculate the total mass ratio. Because in the production process of nylon cotton, there is unevenness in the combing of nylon fibers and unevenness in the spraying of glue by the nozzle. Therefore, the nylon cotton produced in the workshop cannot maintain the same uniformity in every place, so the mass ratio of glue and fiber in each part of the nylon cotton will also be different, which will easily lead to large quality differences in the same batch of nylon wheels, and it is difficult for manufacturers to distinguish the quality of each nylon wheel by naked eyes. This has brought great troubles to the quality control of nylon wheels by manufacturers, which can easily lead to the inability of manufacturers to stably output high-quality nylon wheels. Therefore, it is very necessary to design a method to measure the content of nylon fibers and glue in nylon cotton to solve the above technical problems. Summary of the invention

[0003] The object of the present invention is to solve the above-mentioned problems and shortcomings, and to provide a method for measuring the content of nylon fiber and glue in nylon cotton. The method for measuring the content of nylon fiber and glue in nylon cotton can conveniently and accurately grasp the content of nylon fiber and glue powder in various parts of the nylon cotton, so that the quality of the nylon cotton in various parts can be conveniently and accurately grasped, and then it can be beneficial to produce nylon wheels of required quality according to the quality of various parts of the nylon cotton, and it can be convenient to classify and manage nylon wheels of different qualities, which can bring great convenience to the production enterprises in controlling the quality of nylon wheels, which can facilitate the production enterprises to stably output high-quality nylon wheels.

[0004] The technical solution of the present invention is achieved in this way:

[0005] A method for measuring the content of nylon fiber and glue in nylon cotton is characterized by comprising the following steps:

[0006] Preparation: Cut a piece of nylon cotton after the glue is solidified, and cut the cut nylon cotton into small pieces; weigh out the nylon cotton pieces with a weight of a for later use;

[0007] Dissolution: Add the above-mentioned spare nylon cotton pieces into 20 times the mass of formic acid and stir to fully dissolve them. After the fibers are completely dissolved, continue to soak for half an hour;

[0008] Solid-liquid separation: The mixed solution after immersion is filtered by vacuum filtration to separate the solid and liquid phases, and the filtered solid is dried at 120°C for 1 hour to obtain the mortar powder;

[0009] Weighing: weigh the glue powder after drying to obtain the weight b of the glue powder;

[0010] Calculate the fiber-to-powder ratio: subtract the weight of the glue powder b from the weight of the nylon cotton pieces to get the weight of the nylon fiber c. Use the ratio of the weight of the nylon fiber c to the weight of the glue powder b to calculate the fiber-to-powder ratio of the nylon cotton.

[0011] Preferably, the method for measuring the content of nylon fiber and adhesive in nylon cotton further comprises verifying the solubility of formic acid in nylon fiber, and placing A gram of nylon fiber in 6A gram of formic acid.

[0012] Preferably, the method for measuring the content of nylon fiber and glue in nylon cotton also includes verifying the solubility of formic acid in glue, taking a certain amount of glue liquid and putting it into an oven, baking it at 180°C for 1 hour to obtain a glue solid; taking it out and cooling it, grinding it into small particles of glue solid in a mortar, taking B grams of small particles of glue solid and adding formic acid with a weight greater than or equal to B grams to react for 10 minutes; then filtering out the solid by vacuum filtration, drying the solid in an oven at 120°C for 1 hour to obtain dried glue, and weighing the dried glue; measuring infrared spectra of the finally dried glue and the glue solid without formic acid, and comparing the difference between the two infrared spectra; diluting the formic acid that is not used to dissolve the glue and the formic acid after dissolving the glue with ethanol, respectively, and measuring infrared spectra, and comparing the difference between the two infrared spectra.

[0013] Preferably, after the small-particle slurry solids are ground into small-particle slurry solids in a mortar, several portions of the small-particle slurry solids are weighed, and the weights of at least two portions of the small-particle slurry solids are different; each portion of the small-particle slurry solids is treated in accordance with the above-mentioned method for treating the small-particle slurry solids to verify the solubility of small-particle slurry solids of different weights in formic acid.

[0014] The beneficial effects of the present invention are as follows: by adopting the method for measuring the content of nylon fiber and glue in nylon cotton, the fiber-to-powder ratio of nylon fiber to glue powder in nylon cotton can be measured very conveniently and accurately, which can facilitate nylon wheel manufacturers to accurately calculate the quality of the measured nylon cotton. Such a method can facilitate nylon wheel manufacturers to separately detect the content of nylon fiber and glue powder in various parts of nylon cotton, which can conveniently and accurately grasp the fiber-to-powder ratio in various parts of nylon cotton, so that it can conveniently and accurately grasp the quality of nylon cotton in various parts, and then it can be conducive to correspondingly producing nylon wheels of required quality according to the quality of various parts of nylon cotton, and it can be convenient to classify and manage nylon wheels of different qualities, which can bring great convenience to the production enterprise in controlling the quality of nylon wheels, which can facilitate the production enterprise to stably output high-quality nylon wheels. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The infrared spectra of the adhesive after curing and after adding formic acid and drying in the present invention are shown.

[0016] Figure 2 It is the infrared spectrum of formic acid after dilution with ethanol and formic acid after dissolving the glue in the present invention. DETAILED DESCRIPTION

[0017] The method for measuring the content of nylon fiber and glue in nylon cotton of the present invention comprises the following steps:

[0018] Preparation: Cut a piece of nylon cotton after the glue is solidified, and cut the cut nylon cotton into small pieces; weigh out the nylon cotton pieces with a weight of a for later use;

[0019] Dissolution: Add the above-mentioned spare nylon cotton pieces into 20 times the mass of formic acid, and stir to fully dissolve them (specifically, stir with a glass rod to fully dissolve them). After the fibers are completely dissolved, continue to soak for half an hour;

[0020] Solid-liquid separation: The mixed solution after immersion is filtered by vacuum filtration to separate the solid and liquid phases, and the filtered solid is dried at 120°C for 1 hour to obtain the mortar powder;

[0021] Weighing: weigh the glue powder after drying to obtain the weight b of the glue powder;

[0022] Calculate the fiber-to-powder ratio (the fiber-to-powder ratio refers to the ratio of the weight of nylon fiber to the weight of glue powder): subtract the weight of glue powder b from the weight of nylon cotton pieces to get the weight of nylon fiber c. Use the ratio of the weight of nylon fiber c to the weight of glue powder b to calculate the fiber-to-powder ratio of nylon cotton.

[0023] By adopting the method for measuring the content of nylon fiber and glue in nylon cotton, the fiber-to-powder ratio of nylon fiber to glue powder in nylon cotton can be measured very conveniently and accurately, which can facilitate nylon wheel manufacturers to accurately calculate the quality of the measured nylon cotton. Such a method can facilitate nylon wheel manufacturers to separately detect the content of nylon fiber and glue powder in various parts of nylon cotton, which can conveniently and accurately grasp the fiber-to-powder ratio in various parts of nylon cotton, so that it can conveniently and accurately grasp the quality of nylon cotton in various parts, and then it can be conducive to producing nylon wheels of required quality according to the quality of various parts of nylon cotton, and it can be convenient to classify and manage nylon wheels of different qualities, which can bring great convenience to the quality control of nylon wheels by manufacturers, which can facilitate manufacturers to stably output high-quality nylon wheels.

[0024] In actual use, first take a small amount of nylon cotton blocks from various places of nylon cotton, and use the above method to measure the fiber-to-powder ratios in these nylon cotton blocks respectively; then use these fiber-to-powder ratios to infer the quality of the nylon cotton in various places; finally, according to the quality of the nylon cotton in various places, apply the nylon cotton in various places to nylon wheels of the set quality; this can facilitate nylon wheel manufacturers to accurately classify each nylon wheel according to its quality, which can not only greatly improve the convenience of nylon wheel manufacturers in production management of nylon wheels of different qualities, but also effectively ensure that the quality of nylon wheels sold in batches is highly uniform when selling nylon wheels of uniform quality in batches. Such a method can bring great convenience to nylon wheel manufacturers in quality control of nylon wheels, so that they can output nylon wheels of suitable quality to users very accurately, which can solve a great deal of trouble for nylon wheel manufacturers, and can facilitate manufacturers to stably output high-quality nylon wheels.

[0025] The method for measuring nylon fiber and glue content in nylon cotton also includes verifying the solubility of formic acid to nylon fiber, taking A gram of nylon fiber and putting it into 6A gram of formic acid. The weight of formic acid here is 6 times of the weight of nylon fiber, and in this case, formic acid can quickly dissolve all nylon fibers. It can be seen from this that nylon fiber can be completely dissolved by formic acid, so when nylon cotton pieces are added to the formic acid of 20 times of mass and stirred, the nylon fiber in nylon cotton can be fully and completely dissolved, so that it is extremely accurate to know that the subsequent glue powder weight b measured, and then it can be explained that the method can have very high accuracy and reliability. Make the weight of formic acid 6 times of the weight of nylon fiber, not only can achieve very good verification purpose, but also can control the consumption of related materials, which can make the method for measuring nylon fiber and glue content in nylon cotton have very high applicability.

[0026] When verifying the solubility of formic acid in nylon fiber, 12D nylon fiber can be used. This way, the nylon fiber used to make nylon wheels can be verified, thereby achieving a more accurate and effective verification effect.

[0027] The step of verifying the solubility of formic acid in nylon fiber can be performed before or after any step of directly measuring the nylon cotton after the glue is cured, or simultaneously with any step, so that relevant measurements can be achieved.

[0028] The method for measuring the content of nylon fiber and glue in nylon cotton also includes verifying the solubility of formic acid in glue, taking a certain amount of glue liquid and putting it into an oven, baking it at 180°C for 1 hour to obtain glue solid; taking it out and cooling it, grinding it into small particles of glue solid with a mortar, taking B grams of small particles of glue solid and adding formic acid with a weight greater than or equal to B grams to react for 10 minutes; then filtering out the solid with vacuum filtration, drying the solid in an oven at 120°C for 1 hour to obtain dried glue, and weighing the dried glue; measuring infrared spectra of the finally dried glue and the glue solid without formic acid, and comparing the difference between the two infrared spectra; diluting the formic acid that is not used to dissolve the glue and the formic acid after dissolving the glue with ethanol, and measuring infrared spectra, and comparing the difference between the two infrared spectra. Verifying the solubility of formic acid in the glue in this way can achieve efficient and accurate verification results, thereby being able to very accurately illustrate that formic acid has no solubility in the glue and does not chemically react with the glue. Further, it can be proved that formic acid can be used to separate the fibers and glue solids in nylon cotton to measure the mass ratio of nylon fibers and glue solids. This can prove that the method for measuring the nylon fiber and glue content in nylon cotton can have very high reliability and applicability.

[0029] The step of verifying the solubility of formic acid in the glue can be performed before or after any step of directly measuring the nylon cotton after the glue is cured, or simultaneously with any step, so that relevant measurements can be achieved.

[0030] After the mortar is ground into small particles of glue solid, several portions of small particles of glue solid are weighed, and the weight of at least two portions of small particles of glue solid is different; each portion of small particles of glue solid is processed in the above-mentioned way to verify the solubility of small particles of glue solid in formic acid of different weights. This can make the verification of the solubility of glue solid in formic acid more accurate and reliable.

[0031] When actually verifying the solubility of the mortar solid in formic acid, after grinding into small particles of mortar solid in a mortar, weigh a number of small particles of mortar solid according to the grams listed in the table below (i.e., the mass of the mortar after curing in the table / g), and add each small particle of mortar solid to the corresponding grams of formic acid. After verifying the solubility of the mortar solid in formic acid, the following table and Figure 1 The infrared spectra of the cured glue and the glue after adding formic acid and drying are shown in Figure 1. Figure 2 The infrared spectra of formic acid after dilution with ethanol and formic acid after dissolving the glue are shown in the table below. It can be seen from the analysis of the table below that the quality of the glue after curing remains basically unchanged before and after adding formic acid; Figure 2 Analysis shows that after adding the glue solid to formic acid, its infrared spectrum does not change, indicating that the glue solid is not dissolved in the formic acid, nor does it react with the glue solid. Figure 1 It can be seen that the infrared spectrum of the cured glue did not change after the addition of formic acid, indicating that it did not react with formic acid to generate new substances. In summary, formic acid cannot dissolve the cured glue, nor can it react with it. Previous experiments have shown that formic acid can instantly dissolve nylon fibers, so formic acid can be used to separate the fibers and glue solids in nylon cotton to measure the mass ratio of fibers and glue solids. This method uses formic acid to dissolve the nylon fibers in nylon cotton without dissolving the glue or reacting chemically with the glue, and then uses the solid-liquid separation method to separate the fibers and glue to accurately measure the mass ratio of fibers and glue in nylon cotton.

[0032] Table 1: Comparison of the quality of the cured mortar and the mortar after drying with formic acid

[0033]

[0034] The above embodiments are preferred embodiments of the present invention. All structures similar to the present invention and equivalent changes made thereto should fall within the protection scope of the present invention.

Claims

1. A method for measuring the content of nylon fiber and glue in nylon cotton, characterized in that The following steps are involved: Preparation: Cut a piece of nylon cotton after the glue is solidified, and cut the cut nylon cotton into small pieces; weigh out the nylon cotton pieces with a weight of a for later use; Dissolution: Add the above-mentioned spare nylon cotton pieces into 20 times the mass of formic acid and stir to fully dissolve them. After the fibers are completely dissolved, continue to soak for half an hour; Solid-liquid separation: The mixed solution after immersion is filtered by vacuum filtration to separate the solid and liquid phases, and the filtered solid is dried at 120°C for 1 hour to obtain the mortar powder; Weighing: weigh the glue powder after drying to obtain the weight b of the glue powder; Calculate the fiber-to-powder ratio: subtract the weight of the glue powder b from the weight of the nylon cotton pieces to get the weight of the nylon fiber c. Use the ratio of the weight of the nylon fiber c to the weight of the glue powder b to calculate the fiber-to-powder ratio of the nylon cotton.

2. The method for measuring the content of nylon fiber and glue in nylon cotton according to claim 1, characterized in that: It also includes verifying the solubility of formic acid in nylon fiber, taking A gram of nylon fiber and placing it in 6A grams of formic acid.

3. The method for measuring the content of nylon fiber and glue in nylon cotton according to claim 1, characterized in that: The method also includes verifying the solubility of formic acid in the glue, taking a certain amount of glue liquid and putting it into an oven, baking it at 180°C for 1 hour to obtain a glue solid; taking it out and cooling it, grinding it into small particles of glue solid in a mortar, taking B grams of small particles of glue solid and adding formic acid with a weight greater than or equal to B grams to react for 10 minutes; then filtering out the solid by vacuum filtration, drying the solid in an oven at 120°C for 1 hour to obtain a dried glue, and weighing the dried glue; measuring infrared spectra of the finally dried glue and the glue solid without formic acid, and comparing the difference between the two infrared spectra; diluting the formic acid that is not used to dissolve the glue and the formic acid after dissolving the glue with ethanol, respectively, and measuring infrared spectra, and comparing the difference between the two infrared spectra.

4. The method for measuring the content of nylon fiber and glue in nylon cotton according to claim 3, characterized in that: After being crushed into small-particle slurry solids in a mortar, several portions of the small-particle slurry solids are weighed, and the weights of at least two portions of the small-particle slurry solids are different; each portion of the small-particle slurry solids is treated in the same manner as described above to verify the solubility of small-particle slurry solids of different weights in formic acid.